A comparative investigation of the optical properties of polar and semipolar GaN epi-films grown by metalorganic chemical vapor deposition. (1st June 2022) - Lu, Haixia; Wang, Lianshan; Liu, Yao; Zhang, Shuping; Yang, Yanlian; Saravade, Vishal; Feng, Zhe Chuan; Klein, Benjamin; Ferguson, Ian T; Wan, Lingyu; Sun, Wenhong
Abstract: We report on the structural and optical properties of polar gallium nitride on c-plane sapphire substrates and semi-polar (11–22) GaN films on m-plane sapphire substrates by metalorganic chemical vapor deposition. Polar GaN on c-plane sapphire and semi-polar GaN on m-plane sapphire both show good crystal quality, luminescence, absorption, and Raman characteristics. GaN on c-place sapphire shows a high crystal quality as compared to GaN on m-plane sapphire. Surface roughness of polar GaN is lesser than semi-polar GaN. The biaxial structural stress in GaN switches from compressive to tensile as the temperature is increased. This stress-switch temperature is higher in GaN/c-plane than GaN/m-plane. GaN in polar and semi-polar orientation shows ultraviolet emissions but yellow-emissions are only observed in GaN/c-plane sapphire. Raman spectroscopy-related oscillations show systematic variations with temperature in both GaN configurations (polar and semi-polar). This work provides a framework of characterizations for GaN with different crystal polarities. It contributes towards identifying suitable crystal growth mechanisms based on the application and requirements for doping (In, Al, etc), crystal quality, emission, absorption, and photonic oscillations.